ByzRev 06.2024.043: Georgi Parpulov, Middle-Byzantine Evangelist Portraits: A Corpus of Miniature Paintings (Manuscripta Biblica, Paratextus Biblici 7). Berlin – Boston: De Gruyter 2022. - Rapti, Ioanna (The Byzantine Review, 2024)
Georgi Parpulov, Middle-Byzantine Evangelist Portraits : A Corpus of Miniature Paintings (Manuscripta Biblica, Paratextus Biblici 7). Berlin – Boston: De Gruyter 2022. XIV, 167 pp., 79 plates. – ISBN 978-3-11-075463-6